Health Resort Detox Programs Impact on the Body: a Prospective Laboratory Analysis in «Kivach Clinic» - Fedor I. Isayev; Alexey A. Moskalev (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2022)
INTRODUCTION. The impact on a human organism of health resort detox programs based on therapeutic governance of lymphatic tissues drainage on human metabolism and a possibility to reduce intoxication and inflammation level has not been evaluated yet. AIM. To make the first attempt to objectively estimate the influence of health resort body detoxification programs on lipid and carbohydrate metabolism and the processes of intoxication and inflammation. MATERIAL AND METHODS. The laboratory data were obtained for all the patients treated under the detoxication program in the corresponding date range (89 persons had a venous blood collected on the first day and the day before the departure). The dynamics of the laboratory indicators were calculated. RESULTS AND DISCUSSION. There is an increase of intoxication markers to the end of the first week and a decrease of inflammation and intoxication markers to the end of the second accompanied by a decrease in total cholesterol level. HOMA decreases in all groups, but other insulin resistance markers remain unaltered. The decrease in cholesterol confirms the expected effect of lymphatic drainage and bile acid loss. There is a decrease in the hepatic insulin resistance without a significant change of the total one. The process of autointoxication rising during the lymphatic drainage and its further decline below the start values is confirmed. CONCLUSION. An attempt was made to evaluate the body's detoxification programmes using laboratory markers. Such programs decrease level of total cholesterol, body's intoxication and inflammation level, lower hepatic component of the insulin resistance. This impact is in stages.